Dampak Media Sosial terhadap Prestasi Belajar pada Peserta Didik - Zuliani, Rizki; Luthfiyah, Luthfiyah; Mustikawati, Rara (MASALIQ, 2023)
The objectives of this study are 1) to know the meaning of social media and learning achievement, 2) Knowing the positive and negative impacts of social media, 3)Benefitssocial media on student achievement 4) Social media relations with learning achievement. The type of research used is qualitative research using the library method, collecting data by considering the results review theses, journals, books and studies relevant to the impact of the media social impact on student learning achievement. The data that the author focuses on is data the impact of social media on student learning achievement. Can be concluded that social media greatly affects learning achievement, the influence is in the form of negative influence good or bad, so the role of parents and teachers at school is needed is expected to help students in improving learning achievement through social media.